1998
DOI: 10.1002/(sici)1097-0061(199802)14:3<203::aid-yea205>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of two yeast genes encoding putative isoenzymes of phosphoglycerate mutase

Abstract: Our previous data indicated that GPM1 encodes the only functional phosphoglycerate mutase in yeast. However, in the course of the yeast genome sequencing project, two homologous sequences, designated GPM2 and GPM3, were detected. They have been further investigated in this work. Key residues in the deduced amino acid sequence, shown to be involved in catalysis for Gpm1 (i.e. His8, Arg59, His181) are conserved in both enzymes. Overexpression of the genes under control of their own promoters in a gpm1 deletion m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…¶ The isoenzymes Gpm2p and Gpm3p cannot sustain growth on glucose. They show residual in vivo activity only when they are expressed from a foreign promoter (65). Different hypotheses exist for why Pgilp-deficient mutants do not grow on glucose, e.g., the pentose phosphate pathway in S. cerevisiae is insufficient to support growth and cannot supply the EMP pathway with sufficient amounts of fructose-6-phosphate and glyceraldehydes-3-phosphate (64).…”
Section: Resultsmentioning
confidence: 89%
“…¶ The isoenzymes Gpm2p and Gpm3p cannot sustain growth on glucose. They show residual in vivo activity only when they are expressed from a foreign promoter (65). Different hypotheses exist for why Pgilp-deficient mutants do not grow on glucose, e.g., the pentose phosphate pathway in S. cerevisiae is insufficient to support growth and cannot supply the EMP pathway with sufficient amounts of fructose-6-phosphate and glyceraldehydes-3-phosphate (64).…”
Section: Resultsmentioning
confidence: 89%
“…Indeed, 32 enzymes from Yeast 1.0 were considered insufficiently evidenced and have been removed, whilst a number of metabolites were relocalised to a different compartment. A typical example of an enzyme removed from the reconstruction is Gpm2p; whilst a homologue of Gpm1p, its phosphoglycerate mutase activity could not be evidenced and may be non-functional [18]. Four reconstructions are compared in Figure 2 in terms of enzymes present.…”
Section: Resultsmentioning
confidence: 99%
“…TDH1 encodes a glyceraldehyde 3-phosphate dehydrogenase isoform, which is responsive to NADH stress (Valadi et al 2004), and downregulated in evolved strains as a consequence of improved xylose utilisation (Karhumaa et al 2009;Linck et al 2014). GPM2 encodes a phosphoglycerate mutase which, however, is not the major isoform in glycolysis (Heinisch et al 1998). Both TDH1 and GPM2 have also been associated with phospholipid metabolism (Feddersen et al 2007;Gsell et al 2013), although no specific role has been revealed so far.…”
Section: Discussionmentioning
confidence: 98%